2018
DOI: 10.3346/jkms.2018.33.e222
|View full text |Cite
|
Sign up to set email alerts
|

Subnormal Binocular Contrast Sensitivity Summation in Patients with Intermittent Exotropia

Abstract: BackgroundTo evaluate binocular summation ratio using contrast sensitivity (CS) testing and correlation between binocular summation and stereoacuity, and control scale in intermittent exotropia (IXT).MethodsWe conducted a prospective case-control study. Thirty-seven IXT and 41 controls were evaluated with both monocular and binocular CS testing. We compared the binocular summation ratio of IXT to that of controls. Near and distance stereoacuity was assessed and office-based control scale was evaluated. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It might be helpful to assess the deterioration of alignment in IXT 15 . Jeong found that binocular CS summation ratio was correlated with the control scale in IXT and could be a useful method of assessing binocular visual function in IXT 20 . We supposed BiS in IXT have more improvement than that in other types of strabismus after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…It might be helpful to assess the deterioration of alignment in IXT 15 . Jeong found that binocular CS summation ratio was correlated with the control scale in IXT and could be a useful method of assessing binocular visual function in IXT 20 . We supposed BiS in IXT have more improvement than that in other types of strabismus after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Livingstone and Hubel [ 12 ] showed that stereopsis is also mediated by the magnocellular pathway. Kwon and Jung [ 13 ] used the Optec 6500 vision testing system in IXT and illustrated that the binocular CS summation ratio of low spatial frequencies under photopic conditions was negatively correlated with stereopsis, and suggested its association with the magnocellular pathway. In our study, a poor CS at 1.8, 2.9, 4.5, and 7.1 cpd was associated with more inferior stereopsis, regardless of the presence or absence of the glare stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a poor CS at 1.8, 2.9, 4.5, and 7.1 cpd was associated with more inferior stereopsis, regardless of the presence or absence of the glare stimulus. This range of spatial frequencies (1.8 to 7.1 cpd) includes 3 cpd, which is a low spatial frequency that was significantly correlated with stereopsis according to Kwon and Jung [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CS test represents the spatial resolution of the visual system, which can be abnormal in many diseases including amblyopia, optic neuritis, cataract, glaucoma, strabismus, and brain lesion 4 , 5 . Several studies have investigated CS in exotropia patients under different conditions, such as the presence or absence of glare and degree of illumination 6 9 . However, to date, only a limited number of studies have evaluated the changes in monocular and binocular CS according to surgical outcomes after strabismus surgery.…”
Section: Introductionmentioning
confidence: 99%